Rozklady terytorialne cen płaconych przez konsumentów za warzywa w Polsce - Kędelski, Mieczysław (Wydział Prawa i Administracji UAM, 1971)
Territorial distribution of consumption plays a mayor role in relations betweeen market elements and socio-economic spatial structure of the country. This distribution is determined by numerous factors which have greater or less influence on the structure of effective demands of individual regions. By means of statistical methods the author analyzes the regional differences of consumer prices of vegetables in Poland and studies selected factors defining the degree of differences existing in heterogeneous production and market conditions. In the case of vegetables we are dealing with a group of closely knit components. Vegetables, as articles of consumption, are a separate nutritive group. As a garden yield, however, they are a marginal production of significant price elasticity of an areal structure. Hence the author is justified in verifying the forces existing in the complex of vegetable prices in a regional conception.
Territorial Distribution of Consumers' Prices of Vegetables in Poland